Institutional Reform for Innovation and Entrepreneurship: An Agenda for Europe - Elert, Niklas (SpringerBriefs in Economics, 2017)
entrepreneurship; innovation; Horizon 2020; capital gains; taxation; income; rights; R&D policy; technology; commercialization; financing; investment